Evaluasi Penyimpanan Obat High Alert Di RSUD Dr. Murjani Sampit - lonika, Tesa; Pratomo, Guntur Satrio; Ardhany, Syahrida Dian (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
High Alert drugs are drugs that have a high risk of causing serious injury if they are used incorrectly. Drug management in hospitals is an important aspect in ensuring patient safety and the quality of medical services, especially for drugs that are classified as High Alert. This study aims to evaluate the High Alert drug storage system at RSUD Dr. Murjani Sampit to identify potential risks and implement the required standards. Data was collected by making direct observations using a checklist sheet for evaluating the suitability of storing High Alert drugs in the Pharmacy Warehouse at Dr. RSUD. Murjani Sampit. Percentage of suitability for storing High Alert drugs in the Pharmacy Warehouse at RSUD Dr. Murjani Sampit obtained results of 100% for High Alert drugs in the LASA (Look Alike Sound Alike) category, 100% for High Alert drugs in the high concentrate electrolyte category and 100% for High Alert drugs in the cytostatics category with indicators of suitability for storing High Alert drugs based on Minister of Health Regulations Republic of Indonesia Number 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. Keywords: Evaluation of Storage Suitability, High Alert drugs, RSUD Dr. Murjani Sampit.